2009
DOI: 10.1016/j.jjcc.2009.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous asymptomatic coronary artery dissection in a young man

Abstract: Spontaneous coronary artery dissection (SCAD) is a rare condition that most often presents as acute coronary syndrome or sudden cardiac death. Here we present the case of a young man of 25 years, who had remained asymptomatic in spite of SCAD. This case highlights the fact that spontaneous dissections can occur at a young age and can involve more than one coronary artery, without producing clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…3 Asymptomatic presentation of SCAD is very rare and our search of the literature found only one case report of SCAD in asymptomatic adult men. 4 The present manuscript reported a SCAD in a very young, 18-year-old patient, suggesting that SCAD should be considered in any age group with unexplained myocardial infarction.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…3 Asymptomatic presentation of SCAD is very rare and our search of the literature found only one case report of SCAD in asymptomatic adult men. 4 The present manuscript reported a SCAD in a very young, 18-year-old patient, suggesting that SCAD should be considered in any age group with unexplained myocardial infarction.…”
Section: Discussionmentioning
confidence: 60%
“…Using antiplatelet, even with GPIIb/IIIa, beta-blocker and some cases with heparin, showed successful and spontaneous closure of the dissection. 2,4,6 This patient was treated using medical therapy with antiplatelet, beta blocker, and ace inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The medical, interventional, and surgical management approaches have all been reported to be effective [21,22]. The overall prognosis mandates close follow-up of patients with SCAD, as one cohort study reported a recurrence rate of SCAD as high as 29.4% in 10 years, predominantly in females [23].…”
Section: )mentioning
confidence: 99%
“…However, multi-vessel dissection involvement [1] has been identified which generally requires intervention. Asymtomatic cases are rare and are diagnosed incidentally [2,3]. We present a case of asymptomatic SCAD which was managed conservatively; we also review the literature and various treatment options.…”
Section: Introductionmentioning
confidence: 98%